Tree Diversity, Stand Structure and Community Composition of Tropical Forest in Eastern Ghats of Tamil Nadu, India - Tamilselvan, B.; Sekar, T.; Anbarashan, M. (Indian Forester, 2021)
rest of Eastern Ghats is degrading due to various anthropogenic pressures. In a present study to assess the tree diversity and population structure in the tropical forest of Javadhu hill Eastern Ghats, Tamil Nadu, India, total of 62 tree species belonging to 44 genera and 23 families and 5140 stems were enumerated in 10 ha plots. Memecylon umbellatum was the predominant tree species followed by Psydrax dicoccos, Chloroxylon swietenia and Anogeissus latifolia. The mean density was 514 stems ha-1 and the density of trees ranged from 469-623 ha-1. The basal area in all the study plots ranged from 19.4 m2/ha to 33.2 m2/ha and the mean basal area for the 10 ha plots was 19.87 m2/ha. All top five species had greater density and basal area in 30-90 cm girth class. The Euphorbiaceae are taxonomically diverse and constituted the most-speciose family followed by Combretaceae. The species richness of deciduous species was greater followed by evergreen and brevi-deciduous. The present study reveals that the forest ecosystem restores considerable tree diversity here which is under more threat due to anthropogenic pressure. Therefore, immediate conservation measure is required to preserve the vanishing forest resources.